The OLCI Neural Network Swarm (ONNS): A Bio-Geo-Optical Algorithm for Open Ocean and Coastal Waters - Hieronymi, Martin; Müller, Dagmar; Doerffer, Roland (Frontiers in Marine Science, 2017)
The processing scheme of a novel in-water algorithm for the retrieval of ocean color products from Sentinel-3 OLCI is introduced. The algorithm consists of several blended neural networks that are specialized for 13 different optical water classes. These comprise clearest natural waters but also waters reaching the frontiers of marine optical remote sensing, namely extreme absorbing or scattering waters. Considered chlorophyll concentrations reach up to 200 mg m-3, non-algae particle concentrations up to 1500 g m-3, and the absorption coefficient of colored dissolved organic matter at 440 nm is up to 20 m-1. The algorithm generates different concentrations of water constituents, inherent and apparent optical properties, and a color index. In addition, all products are delivered with an uncertainty estimate. A baseline validation of the products is provided for various water types. We conclude that the algorithm is suitable for the remote sensing estimation of water properties and constituents of most natural waters.